SYMBOLS OF HEROISM IN THE LITERATURE OF THE PEOPLES OF THE GREAT SILK ROAD - Shodieva Madina Nuralievna; Li Xiaoyi 李晓一 (Web of Journals Publishing, 2025)
The article presents the specific features of the heroic image in the literature of the peoples of the Great Silk Road, mainly expressed through such qualities as courage, patriotism, intelligence, loyalty and struggle for justice. A comparative analysis is made of Alpomish in the epic poem "Alpomish" and Sun Ukun in the novel "Journey to the West".
Keywords: Great Silk Road, hero, people, legendary, justice, epic and legendary powers, culture.